Can Green Market Orientation Improve MSME Marketing Performance Through Organizational Ambidexterity? - Bogy Febriatmoko; Widya Prananta; Angga Pandu Wijaya (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2023)
There are environmental issues in many nations, including Indonesia. The preservation of the environment must continue to be the focus of sustainable national development. Small, micro, and medium-sized enterprises (MSMEs) are among the commercial entities that play a significant role in national growth. This study's main objective is to ascertain how innovation capacity and a green market orientation affect MSMEs' marketing success. 117 MSMEs in the city of Semarang make up the study's sample. The process involves using Smart PLS to analyze both the outer and inner models together with any intervening factors. Organizational Ambidexterity, Green Market Orientation, Innovation Capability, and Marketing Performance are the variables used in this study. The findings of this study indicate that Organizational Ambidexterity, Green Market Orientation, and Innovation Capability are all variables that have an impact on Marketing Performance. Organizational Ambidexterity also has an impact on Marketing Performance to a lesser extent. Then simultaneously show that Green Market Orientation and Innovation capability affect Marketing Performance through Organizational Ambidexterity. Only Innovation Capability on Marketing Performance has no effect. The novelty in this study is an environmental issue that is associated with marketing performance.